Evaluation of Molecular Markers of Mesenchymal Phenotype in Melanoma - Mikesh, Leann M. (2010)
Epithelial to mesenchymal transition is a developmental process allowing epithelial cells to dedifferentiate into cells displaying mesenchymal phenotypes. The pathological role of EMT has been implicated in invasion and metastasis for numerous carcinomas, yet limited data exist addressing whether mesenchymal transition (MT) occurs in malignant melanoma cells. Our group developed an in vitro 3D culture system to address MT in melanoma cells upon TGF-β/TNF-α treatment. Loss of E-cadherin is one of the best indicators of MT in epithelial cells. Not surprisingly, E-cadherin was expressed in only three of twelve (25%) melanoma cell lines and all three mesenchymal proteins, N-cadherin, vimentin, and fibronectin, were expressed by seven (58%) lines. However, following cytokine treatment, two or more mesenchymal proteins were elevated in nine (75%) lines. Data support the TGF-β production by melanoma cells which may induce/support MT. Evaluation of E-cadherin, N-cadherin, and Snail expression in melanoma tissue samples are consistent with an inverse coupling of E-cadherin and N-cadherin expression, however, there are also examples suggesting a more complex control of their expression. These results indicate that malignant melanoma cell lines are susceptible to MT following cytokine treatment and highlight the importance of understanding the effects of cytokines on melanoma to undergo MT.